3-dimensional electrode structure for enhanced electrochemical performance of in-plane microsupercapacitors - Wang, Jing Yuan (Nanyang Technological University, 2020)
This thesis focuses on the enhancement of electrochemical performance of in-plane microsupercapacitor including electric double layer capacitor (EDLC) and pseudocapacitors. Enhancement was achieved through a facile synthesis method in which 3-dimensional interconnected nanowire network was obtained. Used as a template for deposition of electroactive material, the nanostructure allows large interfacial area where charge transfer can efficiently occur. The thick layer also permits high material loading to achieve high areal capacitance and energy density performance. Both metal oxide and Polypyrrole-based microsupercapacitor fabricated with the nanostructure design showed remarkable capacitance and energy density performance. Lastly, efforts were made to enhance the electrochemical cycling performance of Polypyrrole-based microsupercapacitor through the investigation of Polypyrrole anionic dopants and electrolytes effect. Large anionic dopant produced mechanically robust Polypyrrole which reduced material swelling and de-doping during charge and discharge process resulting in superior electrochemical cycling performance.